VALIDATION OF AN AUTOMATED WIRELESS SYSTEM FOR SLEEP MONITORING DURING DAYTIME NAPS - Cellini, Nicola (Behav Sleep Med, 2014)
An automated wireless system (WS) for sleep monitoring was recently developed and validated for assessing nighttime sleep. Here, we aimed to evaluate the validity of the WS to correctly monitor daytime sleep during naps compared to polysomnography (PSG). We found that the WS underestimated wake, sleep onset latency, wake after sleep onset, and overestimated total sleep time, sleep efficiency and duration of REM sleep. Sensitivity was moderate for wake (58.51%) and light sleep (66.92%) and strong for deep sleep (83.46%) and REM sleep (82.12%). These results demonstrated that the WS had a low ability to detect wake and systematically over-scored REM sleep, implicating the WS as an inadequate substitute for PSG in diagnosing sleep disorders or for research in which sleep staging is essential.